Sounds from the Eocene: the first singing cicada from the Messel Pit, Germany - Hui Jiang; Maxwell S. Moulds; Stephan M. Blank; Jes Rust; Sonja Wedmann (Scientific Reports)
Abstract Cicadidae is one of the most species-rich insect families today. However, compared to the number of extant species, fossil records of Cicadidae are extremely limited. Among singing cicadas, the tribe Platypleurini within the Cicadinae subfamily is notable for its broad geographic distribution, high species diversity, and distinctive features, but no reliable fossil records have been discovered to date. In this study, we report the first fossil record of the Platypleurini from the Eocene Messel Pit: a new genus and species, Eoplatypleura messelensis. This species not only represents one of the earliest known fossil crown-group Cicadidae from the Eurasian continent but also the oldest confirmed record of the subfamily Cicadinae worldwide to date. As the first described fossil singing cicada from the Eocene Messel Pit, this discovery enriches the species diversity of the Messel biota and fills a significant gap in the Eocene cicada fossil record. The discovery of E. messelensis gen. et sp. nov. will serve as a fossil calibration point for future molecular phylogenetic studies and provides new insights into the origins and dispersal patterns of Platypleurini. Based on the analysis of existing records, Cicadidae was once widely distributed in Germany and across Europe during the Cenozoic.